Reservoir properties and facies characterization from core data and well logging: autochthonous Miocene sediments in the Carpathian Foredeep case study - Shouket, Ali; Jarzyna, Jadwiga (Geology, Geophysics and Environment, 2015)
Laboratory results of total porosity and physical permeability were the basis to calculate Flow Zone Indicator and GR log and porosity log were used for facies identification in the Miocene sandy-shaly sediments in two wells in the Eastern Part of Polish Carpathian Foredeep. There was observed FZI increase with the total porosity from the comprehensive interpretation of logs in the regressive set of parasequences what can be interpreted as better reservoir and hydraulic abilities of them in comparison to transgressive ones. Combining laboratory origin information with well logging results on the basis of facies and FZI correlation worked also as a kind of data scaling.